A community for students. Sign up today!
Here's the question you clicked on:
 0 viewing

This Question is Closed

sauravshakya
 2 years ago
Best ResponseYou've already chosen the best response.3(7)^n 1 = (6+1)^n 1 Now, use binomial coefficient to open (6+1)^n

sauravshakya
 2 years ago
Best ResponseYou've already chosen the best response.3(6+1)^n = nC0 (6)^0 * 1^n + nC1 * 6^1 + 1^(n1)+...+nCn * 6^6*1^0 =1 + nC1*6^1*1^(n1)+...+nCn*6^n *1^0 This gives, (6+1)^n1 = nC1*6^1*1^(n1)+...+nCn*6^n *1^0

sauravshakya
 2 years ago
Best ResponseYou've already chosen the best response.3Now, u can take 6 common from all the terms of (7)^n1. Thus, it is divisible by 6 for all n>=1

Coolsector
 2 years ago
Best ResponseYou've already chosen the best response.2just add another way  by induction check for n =1 we get 6/6 check for n = 2 we get 48/6 = 8 now lets assume that it is correct for n =k now check for n= k+1 [7^(k+1) + 1] / 6 = (7*7^k + 1 )/6 = (6*7^k + 7^k + 1 )/6 = 6*7^k/6 + (7^k + 1)/6 the first term becomes 7^k and the second by is divisible by our assumption.
Ask your own question
Ask a QuestionFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.